2021
DOI: 10.3390/ijms23010158
|View full text |Cite
|
Sign up to set email alerts
|

Functions of COP1/SPA E3 Ubiquitin Ligase Mediated by MpCRY in the Liverwort Marchantia polymorpha under Blue Light

Abstract: COP1/SPA1 complex in Arabidopsis inhibits photomorphogenesis through the ubiquitination of multiple photo-responsive transcription factors in darkness, but such inhibiting function of COP1/SPA1 complex would be suppressed by cryptochromes in blue light. Extensive studies have been conducted on these mechanisms in Arabidopsis whereas little attention has been focused on whether another branch of land plants bryophyte utilizes this blue-light regulatory pathway. To study this problem, we conducted a study in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…We also found that blue light‐induced genes are partially de‐repressed in dark‐grown Ppcop1 and Ppspa mutants, although to a much lesser extent than that in the respective Arabidopsis mutants. In Marchantia polymorpha , in contrast, MpSPA and MpCRY both promoted symmetric growth of the thallus in blue light and thus do not have opposite functions (Zhang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that blue light‐induced genes are partially de‐repressed in dark‐grown Ppcop1 and Ppspa mutants, although to a much lesser extent than that in the respective Arabidopsis mutants. In Marchantia polymorpha , in contrast, MpSPA and MpCRY both promoted symmetric growth of the thallus in blue light and thus do not have opposite functions (Zhang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that the WD–CCE interaction is ancestral, whereas the kinase–PHR interaction may have evolved after the separation of bryophyte and vascular plant lineages. However, it was reported recently that the cryptochrome of the liverwort Marchantia polymorpha interacted via its PHR domain with the kinase domain of MpSPA, although in a blue light‐independent fashion (Zhang et al., 2021). Hence, it remains to be determined whether an AtCRY1‐type or an AtCRY2‐type cryptochrome is ancestral.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular plants, CRY photooligomerization is necessary for blue light signal transduction, phosphorylation, light‐dependent proteolysis, and interaction with proteins (Liu et al ., 2020). It has also been reported that MpCRY interacts with MpSPA in the nucleus under both dark and blue light conditions (Zhang et al ., 2021). These results suggest that MpCRY undergoes oligomerization and interaction with cryptochrome‐interacting proteins in darkness, which might be in preparation for subsequent signal transduction after blue light irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Bryophytes and vascular plants diverged from their common ancestor, which was a bona fide early land plant (McDaniel, Marchantia polymorpha, which is a member of the Bryophyta, is a shade-loving plant (Mache & Loiseaux, 1973) and may have acquired many derived traits to adapt to such environments over the past million years. MpCRY was first identified as a blue light receptor in the M. polymorpha genome (Bowman et al, 2017), and MpCRY was involved in asymmetrical thallus growth, sucrose metabolism, and carbon fixation in M. polymorpha under blue light conditions, but it is unclear how it transduces blue light signaling (Li et al, 2021;Zhang et al, 2021). In this study, we first found that MpCRY self-interaction occurs under dark conditions and that blue light promotes this process (Figs 2, S2), which is different from blue light-dependent oligomerization in vascular plants (Liu et al, 2020).…”
Section: Mpcry Has Distinct Photooligomerization and Protein Degradat...mentioning
confidence: 99%